Fatty Ester‐Based Hydroxy Carbamates – Synthesis and Investigation as Lubricant Additives. Issue 11 (8th October 2018) - Täufer, Amely; Vogt, Markus; Schäffner, Benjamin; Baumann, Wolfgang; Köckritz, Angela
Abstract : The ring opening of carbonated methyl oleate with primary and secondary monoamines is described leading to a range of new hydroxy carbamate esters. The aminolysis of the ester group is observed as a side reaction to varying degrees. A time‐resolved NMR experiment shows that the ring opening runs faster than the amide formation if decylamine is used as nucleophile. Both hydroxy carbamate esters and amides are isolated by column chromatography and characterized. Practical Applications : An application as lubricant additive with improved properties seems to be possible after fine tuning and optimization of the structure of such hydroxy carbamates. Another opportunity might be the crosslinking of such multifunctional compounds, for example, for the formation of bio‐based polyurethane foams. The cyclic carbonate of methyl oleate is cleaved by both primary and secondary monoamines to the respective vicinal hydroxy carbamates. The tribological properties of two products are tested. Abstract : The cyclic carbonate of methyl oleate is cleaved by both primary and secondary monoamines to the respective vicinal hydroxy carbamates. The tribological properties of two products are tested.